The development of a novel serotyping-NS1-ELISA to identify serotypes of dengue virus - Chunya Puttikhunt (2018)
Background: Dengue virus (DENV), which causes mosquito-borne disease dengue hemorrhagic fever (DHF), consists of four serotypes co-circulating in endemic areas. Currently, DENV serotypes can be identified by laborious virus isolation followed by immunofluorescent assay and sophisticated RT-PCR. Objective: To establish a new assay designated as "serotyping-NS1-ELISA" to detect the NS1 protein and to identify DENV serotypes simultaneously. Study design: The monoclonal antibodies (Mabs) against NS1 of each DENV serotype were produced and characterized for their serotype-specificity. To develop serotyping-NS1-ELISA, the selected serotype-specific anti-NS1 Mabs were applied to detect the NS1 antigen, which was previously captured by a flavivirus cross-reactive anti-NS1 Mab. Serotyping accuracy of the developed assay was validated with NS1 from DENV-infected cell culture supernatants and from well-characterized clinical specimens. Results: Of 30 anti-NS1 Mabs, 1 serotype-specific anti-NS1 Mab to each DENV serotype was selected based on NS1 capture ELISA results for developing the serotyping-NS1-ELISA. Using DENV-infected cell culture supernatants for validation, the selected antibodies were shown to be capable of differentiating four DENV serotypes. When acute phase plasma from DENV-infected patients was used for validation, 65 out of 85 specimens (76.5% overall sensitivity) were positive to one of the four serotypes developed in our assay. Interestingly, identification of DENV serotypes by our serotyping-NS1-ELISA was 100% accurate for DENV1, 3 and 4 and 82.4% for DENV2 as compared with standard RT-PCR. Assay specificity was 100% (90/90). Conclusions: The developed serotyping-NS1-ELISA provides an alternative for simultaneous detection of DENV NS1 and identification of its serotype in acute patients' specimens. The assay would be applicable for dengue diagnosis and epidemiological studies. © 2011 Elsevier B.V.